2009
DOI: 10.1002/app.30481
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solvent on surface wettability of electrospun polyphosphazene nanofibers

Abstract: Two kinds of biodegradable polymers, poly(e-caprolactone) (PCL) and poly[(alanino ethyl ester) 0.67 (glycino ethyl ester) 0.33 phosphazene] (PAGP), were electrospun by using four different solvents. All PCL nanofibrous mats had similar surface water contact angles independent of solvents. However, it was found that the water contact angles of PAGP nanofibrous mats were 102.2 AE 2.3 , 113.5 AE 2.2 , 115.8 AE 1.4 , and 119.1 AE 0.7 , respectively, when trifluoroethanol, chloroform, dichloromethane, and tetrahydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…PAGP was synthesized by nucleophilic substitution of corresponding amino acid esters (Beijing Chemical Reagent Co., China) to linear polydichlorophosphazene in the presence of triethylamine as reported before. 28 The linear polydicholorphosphazene was obtained by thermal ring-opening polymerization of hexachlorocyclotriphosphazene (Bo Yuan New Material & Technique Co., Ningbo, China). The molar ratio of alanine ethyl ester to glycine ethyl ester was identified by 1 H NMR (AV600, Bruker, Germany) as 30:70.…”
Section: Methodsmentioning
confidence: 99%
“…PAGP was synthesized by nucleophilic substitution of corresponding amino acid esters (Beijing Chemical Reagent Co., China) to linear polydichlorophosphazene in the presence of triethylamine as reported before. 28 The linear polydicholorphosphazene was obtained by thermal ring-opening polymerization of hexachlorocyclotriphosphazene (Bo Yuan New Material & Technique Co., Ningbo, China). The molar ratio of alanine ethyl ester to glycine ethyl ester was identified by 1 H NMR (AV600, Bruker, Germany) as 30:70.…”
Section: Methodsmentioning
confidence: 99%
“…PGAP was synthesized according to a reported method as shown in Scheme 1. 29 Briefly, linear polydichlorophosphazene, prepared from thermopolymerization of hexachlorophosphazene, was dissolved into anhydrous benzene, followed by adding alanine ethyl ester and triethylamine solution in dry benzene to allow replacement of $ 60 mol % of chlorine atoms. Subsequently, an excess of glycine ethyl ester and triethylamine solution in dry benzene was added to replace the residual chlorine atoms.…”
Section: Synthesis Of Pgapmentioning
confidence: 99%
“…28 For polyphosphazene, the honeycomb-patterned films formed under high humidity could theoretically have different elements composition on film surface in comparison with flat ones, because the phosphorus and nitrogen atoms might interact with H 2 O molecules and migrate toward surface. 29 This study was to evaluate the osteocompatibility of honeycomb-patterned surface topography of amino acid-substituted polyphosphazene film, where a simple and good filmforming polyphosphazene, poly(glycine ethyl ester-co-alanine ethyl ester)phosphazene (PGAP) was synthesized as a model and fabricated into honeycomb-patterned films. With the analysis of scanning electron microscope (SEM), atomic force microscope (AFM), water contact angle, and protein adsorption measurement, surface features like roughness and chemical composition were determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that a fiber diameter decrease and surface roughness increase led to the decrease in wettability . An electrospun mat that has a more rough surface compared with its solvent‐casting equivalent film results in a greater contact angle with water . These studies were mainly carried out using only water as the testing liquid with high surface tension, and therefore, the information about wettability can be distorted.…”
Section: Resultsmentioning
confidence: 99%